Growing Together : Reducing Rural Poverty in Myanmar - Myint, Nikolas (World Bank, Yangon, 2016)
Policies that enable rural communities to participate in expanding economic opportunities can be central to inclusive growth in Myanmar. Rural communities are home to the majority of Myanmar’s population, the majority of its many ethnic groups, and 70 percent of its poor. Development in rural areas is constrained by low returns to agriculture, and significantly lower levels of public service delivery and human development outcomes relative to urban areas. Reforms to enhance agriculture productivity are necessary though not sufficient for improving the welfare and livelihoods of rural communities. These have to be complemented with increased access to social and economic services that can raise human and physical capacity to create the conditions necessary for the growth of a dynamic rural non-farm sector. These reforms could help to not only reduce the drag on rural growth and poverty reduction, but also contribute to structural economic transformation so that the welfare of all people in Myanmar can grow together.